2011
DOI: 10.1253/circj.cj-11-0068
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Patent Foramen Ovale in Chinese Patients With Paradoxical Embolism - Immediate Results and Long-Term Follow-up -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp atent foramen ovale (PFO) is an anatomical variant of the interatrial septum with an overall prevalence of 27% in autopsy studies. 1 PFO has been associated with cryptogenic stroke and migraine headaches, 2-4 and increasingly recognized as a source of paradoxical embolism. A high prevalence of PFO has been reported in approximately 50% of patients with cryptogenic transient ischemic attack (TIA) or ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Doping PEDOT:PSS film with 2,3,5,6-tetrafluoro-7,7,8,8- 2, 02004 (2018) cyanoquinodimethane (F4-TCNQ) [64] increases the work function of the HTL from 5.08 eV to 5.18 eV (Figure 9a), whereas Huang et al [65] achieved similar outcome using dopamine (DA) (Figure 9b). The work function of PE-DOT:PSS was tuned by Lim et al [32] using self-organized HEL (SOHEL), which was composed of PEDOT:PSS and tetrafluoroethylene-perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid copolymer (Figure 9c).…”
Section: Doped Pedot:pss Htlmentioning
confidence: 99%
See 3 more Smart Citations
“…Doping PEDOT:PSS film with 2,3,5,6-tetrafluoro-7,7,8,8- 2, 02004 (2018) cyanoquinodimethane (F4-TCNQ) [64] increases the work function of the HTL from 5.08 eV to 5.18 eV (Figure 9a), whereas Huang et al [65] achieved similar outcome using dopamine (DA) (Figure 9b). The work function of PE-DOT:PSS was tuned by Lim et al [32] using self-organized HEL (SOHEL), which was composed of PEDOT:PSS and tetrafluoroethylene-perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid copolymer (Figure 9c).…”
Section: Doped Pedot:pss Htlmentioning
confidence: 99%
“…Reproduced with permission from Ref. [64,65,32] doi: 10.11605/j.pnrs.201802004 Published by Nature Research Society http://nrs.org | 8 Proceedings of the Nature Research Society, 2, 02004 (2018) Conductivity of PEDOT:PSS can easily be modulated by the removal of PSSH chains [72][73][74]. Removal of PSSH chains results in conductive PEDOT rich film.…”
Section: Electrical Conductivity Of Tailored Pedot:pss Htlsmentioning
confidence: 99%
See 2 more Smart Citations
“…While early studies mostly focus on the analysis of ZigBee performance degradation in presence of WiFi interference, it has been shown that significant throughput reductions can also be observed in WiFi networks [1], [4]. This phenomenon has been justified by considering two different main reasons: i) an intrinsic reason, due to vendor-dependent implementation choices that in some cases make difficult the detection of non-WiFi modulated signals or introduce latency times in the receiver operations [5]; ii) an extrinsic reason, due to the higher time resolution needed by ZigBee for detecting channel activity and preventing collisions [6], [7].…”
Section: Introductionmentioning
confidence: 99%